Standar Pelayanan Minimum bagi Anak Berhadapan dengan Hukum Pada Unit Pelayanan Perempuan dan Anak Kepolisian Resort Kota Banda Aceh - M. Iqbal (Kanun Jurnal Ilmu Hukum, 2013)
ABSTRACT: Each child facing with criminal laws either as violator or victim is entitled to get physical, mental, spiritual and social protection based on the principles of the Convention of the Rights of the Child and the Act of Juvenile Court namely non discrimination, the best interests of the child, right to life, the live sustainability and the development and the respect towards the child opinion. The children having problem with law has a right to get especial protection that must be provided by the government and government institutions. The Unit of Women and Children Service is the first meeting point of the Juvenile Justice System of the child. This research aims to obtain the description of the minimum service of standard applied by the Unit of Banda Aceh Resort Police Station, in dealing with the child, the constraints faced in treating them and the efforts to solve the constraints. To gather the data, the library and field research are applied. The data obtained from library and field research then combined and analysed qualitatively. The Unit has applied the principles of the standards towards the child, the obstacles faced are internal and external obstacles and the efforts done are by training and educating the staffs at the Unit, the Detectives and the Assistant of the detectives and all staffs of the Unit in order to empower the human resources of the Unit. The Minimum Service Standards Towards the Child Violating Criminal Laws at the Unit of Women And Children Service of Banda Aceh Police Resort Station